Pharmacological Targeting of Phosphoinositide Lipid Kinases and Phosphatases in the Immune System: Success, Disappointment, and New Opportunities - Ward, Stephen G.; Blunt, Matthew D. (Frontiers in Immunology, 2012)
The predominant expression of the γ and δ isoforms of PI3K in cells of hematopoietic lineage prompted speculation that inhibitors of these isoforms could offer opportunities for selective targeting of PI3K in the immune system in a range of immune-related pathologies. While there has been some success in developing PI3Kδ inhibitors, progress in developing selective inhibitors of PI3Kγ has been rather disappointing. This has prompted the search for alternative targets with which to modulate PI3K signalling specifically in the immune system. One such target is the SH2-domain containing inositol-5-phosphatase-1 (SHIP-1) which de-phosphorylates PI(3,4,5)P3 at the D5 position of the inositol ring to create PI(3,4)P2. In this article, we first describe the current state of PI3K isoform-selective inhibitor development. We then focus on the structure of SHIP-1 and its function in the immune system. Finally, we consider the current state of development of small molecule compounds that potently and selectively modulate SHIP activity and which offer novel opportunities to manipulate PI3K mediated signalling in the immune system.